Pulmonary Infections - High-Resolution Computed Tomography (HRCT) Patterns in Bone Marrow Transplant Patients - Manal Niazi, Neelum Wahid,Naushaba Malik, Muhammad Ashraf Farooq, (Journal of Rawalpindi Medical College, 2016)
Background: To study the high-resolution computed tomography (HRCT) findings in bone marrow transplant patients with pulmonary infection and to determine distinguishing features among the different types of infections. Methods: This study included 109 bone marrow transplant recipients with documented pulmonary infection. High-resolution CT (HRCT) of the chest were performed , and diagnosis was proven soon after onset of symptoms . Diagnosis was confirmed by bronchoalveolar lavage, sputum cytology, response to therapy, biopsy and autopsy. Results: Out of 109 patients 40 were having pulmonary infections due to fungi,38 bacteria,18 viral- cytomegalovirus (CMV), 9 pneomcystis jiroveci pneumonia(PJP )and 4 mycobacterium tuberculosis.Large nodules more than 1cm in diameter were seen in 28 out of 40 patients with fungal pneumonia(70%), 5 of total 38 patients with bacterial pneumonia(13.1%), 3 of 18 patients with viral infection(16.6%). The halo sign was present in 23 out of 28 patients having large nodules with fungal pneumonia(82.1%), 3 of 31 patients with nodular opacities in bacterial pneumonia(9.6%) ,2 patients (11.1%) with viral and none with pneumocystis jiroveci pneumonia. There was no significant difference in the prevalence of the other HRCT patterns including small nodules, groundglass attenuation, and air-space consolidation among viral, bacterial, and fungal infections. Conclusion: The HRCT pattern of large peripheral nodules, nodules with cavitation,visualization of halo sign and peripheral wedge shaped opacities are most suggestive of fungal infection. In our study, large peripheral nodules and the halo sign were statistically more common in patients with fungal infections. Other HRCT patterns are not specific and thus not helpful in differentiating among the various types of pulmonary infections seen in bone marrow transplant patients.